Association Between Parental Problematic Internet Use and Adolescent Depression. - Raphaely, Shiri G.; Goldberg, Simon B.; Stowe, Zachary N.; Moreno, Megan A. (Child Psychiatry & Human Development, 2026)
We examined the association between parental problematic internet use (PIU) and adolescent depression and whether this association varied based on internet-related rules. We recruited adolescents ages 13–18 and their parent using national Qualtrics panels (N = 4592 dyads). Measures included the Problematic and Risky Internet Use Screening Scale (PRIUSS-3), the Patient Health Questionnaire (PHQ-9), and the internet specific parenting practice scale (ISPPS). Parental PIU was associated with symptoms of adolescent depression, including suicidal ideation, even when controlling for adolescent PIU (β = 0.35, 95% CI [0.32, 0.38]). Time-related rules moderated this association in a non-linear way where the association was strongest when time-related rules were unclear / mid-range. The moderation effect was linear for content-related rules, where stricter rules were associated with a weaker association between parent PIU and adolescent depression. Results support clinicians assessing parent PIU when treating depressed adolescents and engaging parents in monitoring their adolescents' internet use content.